2014
DOI: 10.1080/09540121.2014.952220
|View full text |Cite
|
Sign up to set email alerts
|

Spiritual coping predicts CD4-cell preservation and undetectable viral load over four years

Abstract: In this study of 177 people living with HIV, we examined if spiritual coping leads to slower HIV disease progression (CD4 cells, viral load [VL]), and more positive health behaviors (adherence, safer sex, less substance use). Prior research suggests that physicians' assessment of spiritual coping can be an interventional aid in promoting positive spiritual coping. Longitudinal spiritual coping was rated using qualitative content analysis of six-monthly interviews/essays. Positive spiritual coping (65%) was pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 39 publications
0
33
0
2
Order By: Relevance
“…Spiritual coping (SC) was rated on a scale from very negative (−4: severe spiritual struggle, conflict, anger) to very positive (+4: spiritual growth/transformation as a central component of life), based on directed qualitative content-analysis of participants' interviews/essays on coping with HIV and stressful life events 12,14,15 . Further description of this rating scale can be found in Kremer and Ironson,14 as well as the results section of this paper.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Spiritual coping (SC) was rated on a scale from very negative (−4: severe spiritual struggle, conflict, anger) to very positive (+4: spiritual growth/transformation as a central component of life), based on directed qualitative content-analysis of participants' interviews/essays on coping with HIV and stressful life events 12,14,15 . Further description of this rating scale can be found in Kremer and Ironson,14 as well as the results section of this paper.…”
Section: Methodsmentioning
confidence: 99%
“…11 Our previous work found that a general measure of spiritual coping did predict faster disease progression in HIV (as measured by changes in CD4 and viral load [VL] over 4 years). 12 In fact, those with negative spiritual coping lost their CD4 cells 2.25 times faster then those with positive spiritual coping. This finding is consistent with another study (N = 429), which found that spiritual struggles predicted CD4 change over 12-18 months.…”
Section: Literature In Hivmentioning
confidence: 99%
“…Longitudinal SC was a stronger predictor of biological outcomes (CD4 cell preservation and cumulative undetectable viral load) than CL [14]. In fact, only CL towards self but not other-centered CL, was associated with biological outcome [4].…”
Section: Introductionmentioning
confidence: 88%
“…In women, it is unclear if their perceived benefit from giving CL to others is helpful for their own personal SC with HIV. Since SC is a stronger predictor of biological outcome than CL [4,14], future research should examine why women compared to men living with HIV seem to benefit more from SC, taking sexual orientation, ethnicity, socioeconomic status and geographical background into account [5].…”
Section: Discussionmentioning
confidence: 99%
“…Coping, according to Lazarus and Folkman, [8] involves “cognitive and behavioral efforts to manage specific external and/or internal demands that are appraised as taxing or exceeding the resources of the person.” There are adaptive coping strategies (e.g., positive reframing and active coping) and maladaptive coping strategies (e.g., substance use and denial). Research has been done on coping strategies and their relationship to the progression of chronic diseases or conditions like human immunodeficiency virus (HIV), dementia, and pain [912] but very little in the field of ophthalmology. [13,14] We are not aware of any studies that have examined coping strategies and the risk of glaucoma progression.…”
Section: Introductionmentioning
confidence: 99%